Algebra 2 URGENT
posted by Trisan on .
here is my take:
you know that x^-1 = 1/x
so in the denominator you have
(a^-1) - (b^-1) = 1/a - 1/b
you need to have the same denominator, which you get by multiplying both in the numerator and denominatorby the other fraction's denominatior
so you get:
(b/ab)- (a/ab) = (b-a/ ab)
the whole expression looks as this:
(a-b)/[b-a/ab] <=> ab(a-b)/(b-a)
multiplying inside the bracket you get:
[(a^2)b - a(b^2)] / (b-a)
hope this helps...otherwise some other genious may help u :-D ..goodluck.